Short-term outcome of robotic and laparoscopic surgery for gynecological malignancies: A single-center experience - Corina- Elena Minciuna; Mihail Ivanov; Sanziana Aioanei; Stefan Tudor; Monica Lacatus; Catalin Vasilescu (Wolters Kluwer Medknow Publications, 2023)
Objectives: Minimally invasive surgery (MIS) has become the preferred option for many gynecologic pathologies since complication rate and postoperative recovery time have decreased considerably. Postoperative complications remain an important aspect when using the MIS approach, if they are not timely or accurately diagnosed and treated. The main aim of the study is to first assess their incidence, followed by identifying possible risk factors. Furthermore, the secondary aim is to identify if the type of MIS approach used, robotic or laparoscopic, may render some additional benefits. Materials and Methods: The database of the General Surgery Department was queried between 2008 and 2019 for patients with gynecologic pathology: 2907 cases were identified. An additional selection was performed using the following filters: MIS and neoplasia. All emergency surgeries were excluded. One hundred and ninety-eight cases were obtained. Results: The majority of complications were urological (11.6%) with only 7.07% requiring a specific urological procedure. The second most common was lymphorrhea 4.5%. Dindo-Clavien classification correlates positively with the postoperative hospital stay (PHS) (P = 0.000), the type of surgery (P = 0.046), the primary tumor location (P = 0.011), conversion rate (P = 0.049), the expertise of the lead surgeon (P = 0.012), and the operative time (P = 0.002). The urological complications correlate positively with the type of surgery (P = 0.002), the tumor location (P = 0.001), early reintervention (P = 0.000), operative time (P = 0.006), postoperative hemorrhage (P = 0.000), pelvic abscess (P = 0.000), venous thrombosis (P = 0.011), and postoperative cardiac complications (P = 0.002). Laparoscopic and robotic approaches were comparatively assessed. The PHS (P = 0.025), the type of surgery performed (P = 0.000), and primary tumor location (P = 0.011) were statistically significantly different. Conclusion: Postoperative complications reported after MIS for gynecological malignancies show similar incidence as in the current literature, also taking into consideration those for the open approach. The robotic approach seems to be able to perform more complex surgeries with no difference in the postoperative complication rates. The expertise of the lead surgeon in gynecology correlates with lower postoperative complications. Further prospective studies are needed to confirm these results.